Invasive Evaluation of Patients With Angina in the Absence of Obstructive Coronary Artery Disease. Issue 12 (24th March 2015) - Lee, Bong-Ki; Lim, Hong-Seok; Fearon, William F.; Yong, Andy S.; Yamada, Ryotaro; Tanaka, Shigemitsu; Lee, David P.; Yeung, Alan C.; Tremmel, Jennifer A.
<x xml:space="preserve">Abstract</x> Background— More than 20% of patients presenting to the cardiac catheterization laboratory with angina have no angiographic evidence of coronary artery disease. Despite a "normal" angiogram, these patients often have persistent symptoms, recurrent hospitalizations, a poor functional status, and adverse cardiovascular outcomes, without a clear diagnosis. Methods and Results— In 139 patients with angina in the absence of obstructive coronary artery disease (no diameter stenosis >50%), endothelial function was assessed; the index of microcirculatory resistance, coronary flow reserve, and fractional flow reserve were measured; and intravascular ultrasound was performed. There were no complications. The average age was 54.0±11.4 years, and 107 (77%) were women. All patients had at least some evidence of atherosclerosis based on an intravascular ultrasound examination of the left anterior descending artery. Endothelial dysfunction (a decrease in luminal diameter of >20% after intracoronary acetylcholine) was present in 61 patients (44%). Microvascular impairment (an index of microcirculatory resistance ≥25) was present in 29 patients (21%). Seven patients (5%) had a fractional flow reserve ⩽0.80. A myocardial bridge was present in 70 patients (58%). Overall, only 32 patients (23%) had no coronary explanation for their angina, with normal endothelial function, normal coronary physiological assessment, and no myocardial bridging. Conclusions— The majority of patients with angina in the absence of obstructive coronary artery disease have occult coronary abnormalities. A comprehensive invasive assessment of these patients at the time of coronary angiography can be performed safely and provides important diagnostic information that may affect treatment and outcomes.